Redefining Urdu politics in India - Fārūqī, Aṭhar (Oxford Univ. Press, 2006)
Most of the papers presented at the International Conference on Minority Languages, held at New Delhi in 2002
Includes bibliographical references and index
Based on presentations at a conference in New Delhi held in 2002, organized by Zakir Husain Study Circle
Keywords: Konferenzschrift -- 2002 -- Delhi; Konferenz; Sozialer Wandel; Politik; Sprachpolitik; Urdu; Indien